The Influence of Principal Leadership and Academic Supervision on Teachers’ Teaching Performance at SMA Negeri 1 Bitung - Marina Kairupan; Joulanda Altje Meiske Rawis; Romi Junior Mongdong (International Journal of Science and Environment (IJSE), 2026)
This study aims to analyze the influence of principal leadership and academic supervision on teachers’ teaching performance at SMA Negeri 1 Bitung, both partially and simultaneously. This research employed a quantitative approach using an explanatory research method. The population consisted of all civil servant teachers at SMA Negeri 1 Bitung, totaling 31 individuals, with a saturated sampling technique (total sampling) applied. Data were collected through a closed-ended questionnaire using a Likert scale that had been tested for validity and reliability, and were analyzed using multiple linear regression with SPSS software. The results indicate that: (1) principal leadership has a positive and significant partial effect on teachers’ teaching performance, with a value of 3.106 > 2.048; (2) academic supervision has a positive and significant partial effect on teachers’ teaching performance, with a value of 4.002 > 2.048; and (3) simultaneously, principal leadership and academic supervision have a significant effect on teachers’ teaching performance, with a value of 50.008 > 3.34. The coefficient of determination (R²) of 0.625 indicates that these two independent variables contribute 62.5% to the variation in teachers’ teaching performance, while the remaining proportion is influenced by other factors outside the research model. These findings emphasize that the synergy between supportive leadership styles and well-planned academic supervision is a key factor in enhancing teacher professionalism and the quality of learning in schools.